2011
DOI: 10.4161/cib.17871
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction: Neuroimaging findings

Abstract: The Internet has so radically changed the way we conduct our lives for a long time. However, maladaptive use of the internet has resulted in impairment of the individual's psychological well-being, academic failure and reduced work performance. While not yet officially codified within a psychopathological framework, Internet addiction disorder (IAD) is growing both in prevalence and within the public consciousness as a potentially problematic condition with many parallels to existing recognized disorders. Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 29 publications
2
38
0
2
Order By: Relevance
“…Results from neuroimaging experiments have shown neurobiological changes similar to those observed in substance addictions (Yuan et al 2011). These changes include: lower activation in conflict detection, less efficiency in information processing, lower cognitive control, impaired executive control and enhanced reward sensitivity.…”
Section: Psychopathological Modelsmentioning
confidence: 61%
“…Results from neuroimaging experiments have shown neurobiological changes similar to those observed in substance addictions (Yuan et al 2011). These changes include: lower activation in conflict detection, less efficiency in information processing, lower cognitive control, impaired executive control and enhanced reward sensitivity.…”
Section: Psychopathological Modelsmentioning
confidence: 61%
“…All of the above components are criteria for substance dependence [25]. Furthermore, recent neuroimaging findings have associated Internet overuse with neurobiological changes, [65] similar to those observed in addictions. Although much more research is needed, evidence shows that IA shares much more similarities with addictive disorders than with impulse control disorders.…”
Section: Classificationmentioning
confidence: 99%
“…Recent studies of internet addiction using cue-induced functional magnetic resonance imaging (fMRI) have shown that internet addiction, substance abuse and pathologic gambling shared similar brain activity in responses to internet (Han et al, 2011;Han, Hwang & Renshaw, 2010;Yuan, Qin, Liu & Tian, 2011), substance (Franken, 2003;Maas et al, 1998;Wilson, Sayette & Fiez, 2004) and gambling cues (Crockford, Goodyear, Edwards, Quickfall & el-Guebaly, 2005;Goudriaan, de Ruiter, van den Brink, Oosterlaan & Veltman, 2010). For example, fMRI studies of game cue-induced brain activity have noted that excessive online game players show increased activity in the dorsolateral prefrontal cortex (DLPFC), orbitofrontal cortex (OFC), anterior cingulate, nucleus accumbens, and caudate nucleus, relative to a healthy comparison group (Han et al, 2010;Ko et al, 2009).…”
Section: Online Game Addiction and Brain Imaging Findingsmentioning
confidence: 99%